Alexandre Schanne (1823-1887) et l’enfant : de l’art à la fabrication de jouets - Michel Manson (Strenae)
Toy makers participate in the production of objects belonging to children's material culture. My research on the history of toys has drawn my attention to a nineteenth-century toy maker who was also an artist, Alexandre Schanne. This article attempts to reconstruct the history of his company, created by his father, and then to understand how his dual training in fine arts and industrial design made him an unusual toy maker and a precursor of artists fashioning designer toys, adapting creations to the specific child recipient.